Kemitraan Antar Stakeholders dalam Pengembangan Agrowisata di Desa Sungai Langka Kabupaten Pesawaran - Indah Mustika Dewi; Dian Kagungan; Devi Yulianti (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Tourism is one of the potential areas in regional development because it can drive people's economic activities. Agrotourism is a form of tourism that utilizes agricultural land and natural resources to attract tourists. Agrotourism if processed correctly can improve the welfare of its population. Therefore, with more and more agrotourism development will also have an impact on improving the welfare of farmers involved in these activities. Sungai Langka is a village located in the district gedongtataan Pesawaran district that has tourism potential based on agrotourism. Land use in Sungai Langka Village is mostly used in agriculture and plantations. Agrotourism development in Sungai Langka Village is carried out in order to optimize the utilization of plantation land and realize participatory development. This research aims to analyze the partnership model between stakeholders in the development of agrotourism potential in The Village of Sungai Langka Pesawaran This type of research is qualitative. Data collection is done by interview, documentation, and observation. Based on the research that has been done, it can be concluded that the development of agrotourism in Sungai Langka including Community-Based Tourism by using the model of Mutualism partnership that is the alliance of two or more parties who are equally aware of the importance of partnership, namely mutually beneficial, so that it will achieve the objectives optimally. As a consideration, the Department of Agriculture and Tourism in Pesawaran Regency provide training to process agricultural products to women farmers groups and communities, sub-districts and complete facilities and infrastructure as well as promotional aspects.